Preparation method of high-voltage and low-loss iron-nickel magnetic powder core

CN122991790APending Publication Date: 2026-10-27TDG KAIWEI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611181537.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]针对现有金属软磁粉体包覆技术存在的绝缘层均匀性差、高温易失效、成品耐压水平低的缺陷,本发明的目的在于提供一种高耐压和低损耗铁镍磁粉芯的制备方法,通过无机强化、硅源填充、有机硅封孔三层协同包覆工艺,在不损害铁镍粉体原有低损耗、高磁导率性能的前提下,系统性提升包覆层的均匀度、完整性与高温结构稳定性,大幅提升磁粉芯的绝缘耐压能力,同时工艺简洁可控,适配规模化量产

Benefits of technology

1.本发明提供了一种高耐压和低损耗铁镍磁粉芯的制备方法,通过构建无机磷酸盐强化层、硅基填充层、有机硅封孔层的梯度复合绝缘结构:底层磷酸盐层与金属基体结合牢固,构筑基础绝缘骨架;中层硅源层填补底层包覆的微观孔隙与缺陷,提升绝缘层致密度与连续性;外层有机硅树脂层封堵残留缺陷,同时赋予粉体良好的成型性,实现了三层协同包覆,绝缘耐压性能大幅提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122991790A_ABST
    Figure CN122991790A_ABST
Patent Text Reader

Abstract

The application provides a preparation method of a high-voltage and low-loss iron-nickel magnetic powder core and relates to the technical field of soft magnetic composite material preparation. A first layer adopts a phosphate inorganic coating agent to construct an inorganic reinforced insulation layer on the surface of the powder; a second layer adopts a silica sol to achieve nanoscale coating and form a dense silicon dioxide insulation layer; a third layer adopts an organic silicon resin to coat and improve the molding while strengthening the pressure resistance and insulation performance of the coating layer; and then granulation, screening, lubrication, compression molding and annealing treatment are performed to obtain the iron-nickel metal magnetic powder core. The application provides a preparation method of a high-voltage and low-loss iron-nickel magnetic powder core. Through the three-layer synergistic coating process of inorganic reinforcement, silicon source filling and organic silicon resin hole sealing, the uniformity, integrity and high-temperature structural stability of the coating layer are systematically improved without impairing the original low-loss and high-permeability performance of the iron-nickel powder, the insulation pressure resistance of the magnetic powder core is greatly improved, and meanwhile, the process is simple and controllable and is suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of soft magnetic composite material preparation technology, specifically a method for preparing a high-pressure-resistant and low-loss iron-nickel magnetic powder core. Background Technology

[0002] With the rapid development of electronic devices towards higher density and higher performance, the miniaturization and integration of magnetic components such as copper-iron co-fired inductors have become the mainstream trend in the industry. The process of co-firing copper sheets with metal soft magnetic coated powder can achieve structural integration, effectively reducing component size while improving magnetic properties and mechanical strength. However, as component sizes continue to shrink and internal structures become increasingly sophisticated, two major technical bottlenecks are becoming increasingly prominent: First, the insulation withstand voltage performance between the electrode and the magnetic powder decreases, and breakdown easily occurs under high voltage conditions, leading to insulation failure. Secondly, abnormal conduction can easily occur between the two electrodes of a common-mode inductor, which can damage the isolation characteristics and, in severe cases, cause local overheating or even burn out the circuit board. This greatly limits the reliability of the device and its operating condition adaptability. The insulating coating of the metal soft magnetic powder is the core process that determines the resistivity of the magnetic core, the level of eddy current loss, and the isolation effect of the electrode magnet.

[0003] Currently, the mainstream powder coating technologies in the industry mainly include three categories: One method is phosphating, which can generate an amorphous phosphate film on the powder surface. The process is mature and inexpensive, but the insulation layer thickness is only tens to hundreds of nanometers, with limited density and uniformity. It is also weak in resistance to damp heat and thermal shock, and is prone to local defects under high temperature co-firing or high pressure stress, leading to insulation failure. The second method is inorganic salt coating, which involves constructing an inorganic oxide layer through sol-gel or hydrolysis precipitation. It has good thermal stability and hardness, but the interfacial bonding force with the metal powder is greatly affected by the process. The coating layer is brittle and prone to microcracks, and it is easy to break under stress during pressing and sintering. Thirdly, organic resin coating can form a thicker insulating layer and has flexible processing. However, organic resin generally has insufficient heat resistance and will decompose and carbonize during sintering at temperatures above 300°C. This not only results in the loss of insulation performance, but the residual carbon will also contaminate the magnetic core and degrade its magnetic properties.

[0004] The combined defects of existing coating technologies result in generally low insulation withstand voltage levels in finished products: conventional products with an electrode spacing of 1mm have a withstand voltage of only about 10V, and magnetic ring products typically have a withstand voltage in the 50V range, far from meeting the performance requirements of current high power density and high operating voltage inductors. Fundamentally, traditional coating layers cannot simultaneously meet the stringent requirements of structural integrity, interface stability, and high-temperature tolerance at the nanometer / micrometer scale, and cannot adapt to the high-temperature process environment of copper-iron co-firing above 600℃. Therefore, developing a new powder coating technology that can withstand high-temperature sintering and possesses high density, excellent interfacial bonding, and insulation strength in the hundreds of V / mm range is a key material bottleneck driving the upgrade of copper-iron co-fired inductors towards high withstand voltage and miniaturization. Compared to mainstream materials such as iron-silicon-aluminum, silicon-iron, and iron-nickel-molybdenum, iron-nickel soft magnetic powder combines high permeability, high saturation flux density, and controllable high-frequency losses, offering excellent overall cost-effectiveness and making it the preferred matrix material for high-end inductor components.

[0005] However, existing coating processes also suffer from insufficient pressure resistance and poor high-temperature stability when applied to iron-nickel powder, failing to fully utilize its material performance advantages. Therefore, this invention proposes a method for preparing iron-nickel magnetic powder cores with high pressure resistance and low loss, thereby effectively solving the above-mentioned problems and difficulties. Summary of the Invention

[0006] To address the shortcomings of existing metal soft magnetic powder coating technologies, such as poor insulation uniformity, susceptibility to high-temperature failure, and low withstand voltage levels in finished products, this invention aims to provide a method for preparing high-voltage and low-loss iron-nickel magnetic powder cores. Through a three-layer synergistic coating process involving inorganic strengthening, silicon source filling, and organosilicon sealing, the uniformity, integrity, and high-temperature structural stability of the coating layer are systematically improved without compromising the original low-loss and high-permeability properties of the iron-nickel powder. This significantly enhances the insulation and withstand voltage capabilities of the magnetic powder core, while also providing a simple and controllable process suitable for large-scale mass production.

[0007] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a high-pressure-resistant and low-loss iron-nickel magnetic powder core, the method specifically includes the following steps: Step 1: Construction of the inorganic reinforcement layer; FeNi50 alloy powder is mixed evenly with inorganic coating agent and solvent, and after baking, curing, and sieving, a composite powder A with an inorganic reinforced insulating layer on the surface is obtained; Step 2: Silicon source treatment: The composite powder A is mixed evenly with the silicon source coating agent and solvent, and after baking, curing, sieving and dispersing, a composite powder B with an inorganic reinforcing layer and a silicon source insulating layer successively coated on its surface is obtained; Step 3: Silicone resin coating; The composite powder B is mixed evenly with silicone resin binder and solvent, and after wet granulation, baking and pre-curing, and grading and sieving, granules with three layers of insulating structure are obtained on the surface. Step 4: Lubrication and molding; add lubricant to the granular material, mix evenly, and then cold press to obtain a magnetic core blank; Step 5: Heat treatment; The green core blank is placed in a protective atmosphere for annealing heat treatment to eliminate the internal stress of compression and to thermally convert the silicone resin into a heat-resistant insulating structure. After the heat treatment is completed, it is cooled with the furnace to obtain the finished iron-nickel magnetic powder core.

[0008] Furthermore, the laser particle size D50 of the FeNi50 alloy powder is one or more of 3μm, 5μm, 10μm, 15μm, and 20μm.

[0009] Further, the inorganic coating agent in step 1 is one or more of phosphoric acid, zinc dihydrogen phosphate, aluminum dihydrogen phosphate, calcium phosphate, nitrate, silicate, malonic acid, and oxalic acid; the amount of inorganic coating agent added is 6-8 wt% of the FeNi50 alloy powder.

[0010] Furthermore, the baking temperature in step 1 is 100~180℃, and the baking time is 0.5~2h; a 200~300 mesh sieve is used for sieving.

[0011] Further, the silicon source coating agent in step 2 is one or more of water glass, silicon dioxide, orthosilicate, silane coupling agent, and silica sol; the amount of silicon source coating agent added is 0.1~1wt% of the FeNi50 alloy powder mass, the baking temperature is 100~160℃, the baking time is 0.5~2h; and sieving is done using a 200~300 mesh sieve.

[0012] Further, the organosilicon resin in step 3 is one or more of methyl silicone resin, vinyl silicone resin, epoxy modified silicone resin, and phenyl silicone resin; the amount of organosilicon resin added is 1~1.5wt% of the FeNi50 alloy powder mass, and wet granulation is carried out using a 60~80 mesh sieve; the baking temperature is 50~100℃, and the baking time is 0.5~2h; the grading and sieving is carried out using a 60~200 mesh sieve.

[0013] Further, the lubricant in step 4 is one or more of molybdenum disulfide, zinc stearate, mica powder, hexagonal boron nitride, and calcium stearate; the amount of lubricant added is 0.2~0.5wt% of the FeNi50 alloy powder mass; the cold pressing pressure is 13~18T / cm. 2 .

[0014] Furthermore, the protective atmosphere in step 5 is a mixture of nitrogen and hydrogen, wherein the nitrogen flow rate is 10-20 m³ / h. 3 / h, hydrogen flow rate is 0.5~2m 3 / h; the annealing heat treatment temperature is 680~750℃, and the holding time is 0.5~2h.

[0015] This invention provides a method for preparing a high-pressure-resistant and low-loss iron-nickel magnetic powder core. It has the following beneficial effects: 1. This invention provides a method for preparing high-voltage-resistant and low-loss iron-nickel magnetic powder cores. By constructing a gradient composite insulation structure consisting of an inorganic phosphate reinforcing layer, a silicon-based filling layer, and an organosilicon sealing layer: the bottom phosphate layer is firmly bonded to the metal matrix, forming a basic insulation framework; the middle silicon source layer fills the micropores and defects of the bottom layer, improving the density and continuity of the insulation layer; the outer organosilicon resin layer seals residual defects and simultaneously imparts good formability to the powder, achieving synergistic three-layer coating and significantly improving insulation and voltage resistance performance.

[0016] 2. This invention provides a method for preparing a high-voltage-resistant and low-loss iron-nickel magnetic powder core. It exhibits excellent high-temperature stability, is compatible with co-firing processes, and maintains excellent magnetic properties, achieving a balance between low loss and high voltage resistance. The coating process is gentle and does not damage the intrinsic magnetic properties of the iron-nickel powder. By precisely controlling the thickness and uniformity of the coating layer, the high voltage resistance is significantly improved while maintaining the advantages of high magnetic permeability and low high-frequency loss of iron-nickel materials. The inorganic phosphate layer and silicon substrate themselves have excellent heat resistance. The outer organic silicone resin is transformed into a stable silicon-oxygen network structure after high-temperature annealing, which is compatible with the high-temperature process environment of copper-iron co-firing and avoids the drawbacks of high-temperature failure of traditional organic coatings.

[0017] 3. This invention provides a method for preparing high-pressure-resistant and low-loss iron-nickel magnetic powder cores. The process is simple and controllable, with strong adaptability to mass production. The entire process adopts mature kneading, coating, baking and sieving techniques, without the need for harsh reaction conditions and special equipment. The raw materials are all general-purpose chemical products, so the cost is controllable and the batch consistency is good. It can be directly connected to existing magnetic powder core mass production lines and has good industrialization and promotion value. Attached Figure Description

[0018] Figure 1 This is a cross-sectional EDS elemental surface scan diagram of the coated iron-nickel soft magnetic powder of the present invention; Figure 2 For the present invention Figure 1 The corresponding Fe element distribution map; Figure 3 For the present invention Figure 1 The corresponding P-element distribution mapping diagram; Figure 4 For the present invention Figure 1 The corresponding Si element distribution mapping diagram. Detailed Implementation

[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0020] Example 1: like Figure 1-4 As shown in the figure, this invention provides a method for preparing a high-pressure-resistant and low-loss iron-nickel magnetic powder core, the steps of which are as follows: Raw material preparation: Weigh 1000g of FeNi50 (D50=10μm) alloy powder as the base raw material; First coating (phosphate coating): Calcium phosphate solution (added at 8 wt% of FeNi50 powder mass) is mixed with FeNi50 powder and stirred until homogeneous, ensuring full contact between the powder surface and the solution. The mixture is baked at 150℃ for 30 minutes, then removed and sieved through a 300-mesh sieve to obtain composite powder A. Second coating (silica sol coating): Silica sol (1 wt% of FeNi50 powder) and deionized water (4 wt% of FeNi50 powder) are mixed evenly to obtain a pretreatment solution. This pretreatment solution is then thoroughly mixed with composite powder A to ensure uniform wetting of the powder surface. The mixture is baked at 130℃ for 30 minutes, and then passed through a 300-mesh sieve to obtain composite powder B. Third coating (silicone resin coating): Silicone resin (1.2 wt% of FeNi50 powder) and acetone (5 wt% of FeNi50 powder) are mixed evenly to obtain a resin solution. This solution is then mixed evenly with composite powder B and wet-granulated through a 60-mesh sieve. The granulated material is baked at 60℃ for 60 minutes, and then passed through a 60-200 mesh sieve to obtain granules C with a specific particle size distribution. Adding lubricant: Add 0.3wt% zinc stearate of FeNi50 powder as a lubricant to the granules C, and mix evenly to obtain the finished granules D; Compression molding: The finished granules D are made at 16T / cm 2 Under pressure, a toroidal magnetic core blank conforming to the T102 standard is formed; Heat treatment: The green billet was placed in a tube furnace and annealed at 710°C for 1 hour under a nitrogen and hydrogen atmosphere. It was then cooled to room temperature in the furnace to obtain the final molten magnetic ring. The nitrogen flow rate was 15 m³ / h. 3 / h, hydrogen flow rate is 1m 3 / h.

[0021] Example 2: This embodiment is basically the same as Embodiment 1, except that: The second coating replaces the silica sol with nano silica: nano silica powder (added at 0.3 wt% of the FeNi50 powder mass) is mixed with the base raw material and stirred thoroughly to obtain composite powder A. The remaining coating and processing are the same as in Example 1.

[0022] This embodiment uses nano-silica mixture, which has high specific surface area and surface activity. Its synergistic effect with other coatings helps to strengthen the formation of a more uniform and dense insulating layer on the surface of FeNi50 powder, which may further improve the resistivity between powders.

[0023] Example 3: This embodiment is basically the same as Embodiment 1, except that: The second coating replaces the silica sol with nano-alumina: nano-silica powder (added at 0.3wt% of the FeNi50 powder mass) is mixed with the base raw material and stirred thoroughly to obtain composite powder A. The remaining coating and processing are the same as in Example 1.

[0024] Comparative Example 1: This embodiment is basically the same as Embodiment 1, except that: Second coating (KH550 coating): KH550 (added at 1 wt% of FeNi50 powder mass), ethanol, and deionized water (added at 3 wt% and 1 wt% of FeNi50 powder mass, respectively) were mixed evenly to obtain a pretreatment solution. This pretreatment solution was then thoroughly mixed with the FeNi50 powder to uniformly wet the powder surface. The mixture was baked at 130°C for 30 minutes, and then passed through an 80-mesh sieve to obtain composite powder A. The remaining coating and treatment processes were the same as in Example 1.

[0025] Comparative Example Comparative Examples 2 to 10 are provided, which are substantially the same as Example 1, with the differences shown in Table 1: Table 1: Parameter comparison between each comparative example and Example 1 Table 2: Magnetic ring characteristic data of powder materials; Note: The magnetic ring dimensions are: inner diameter 5.10mm, outer diameter 10.20mm; Comparative Example 1 uses a traditional coating process, which has virtually no insulation and withstand voltage.

[0026] For Example 1 and Comparative Examples 2 to 10, while the pressure resistance level was improved, the initial sensitivity was not worse than that of the respective comparisons; Analysis of the test results shows that: Example 1 employed a three-layer coating of calcium phosphate, silica sol, and organosilicon resin, combined with 300-mesh fine sieving, to achieve optimal overall performance: a withstand voltage of 400V, far exceeding all comparative examples, while the power loss was only 450kW / m. 3 The magnetic permeability remains at 70, achieving an excellent balance between high withstand voltage and low loss; Examples 2 and 3 use dry mixing of nano-oxides as an intermediate layer, which slightly improves the magnetic permeability, but reduces the withstand voltage to 200V and increases the loss. This indicates that the uniformity and defect filling effect of wet silica sol coating are better than those of dry nano-powder mixing. Comparative Example 1, which uses a traditional silane coupling agent for coating, has a pressure resistance of almost 0 and a significant increase in loss, indicating that the coating effect of the traditional silane coupling agent as a silicon source is far worse than that of silica sol coating. Comparative Example 2 shows that when the coating order is reversed, the withstand voltage drops significantly to 50V, indicating that the order of first applying inorganic phosphate and then filling with silicon source is the key to ensuring the integrity of the insulation layer structure. Reversing the order makes it impossible to form a continuous and dense insulation skeleton. Comparative Examples 3-7 show that when the amount of calcium phosphate added is insufficient or the amount of silica sol added is too low, the insulation layer is discontinuous and the withstand voltage performance drops sharply; only when the amount of phosphate and silicon source added reaches a reasonable threshold can an effective insulation structure be formed. Comparative Examples 8-10 show that the mesh size (i.e. the degree of powder dispersion) has a significant impact on the pressure resistance performance. The lower the mesh size, the more serious the powder agglomeration, the worse the coating uniformity, and the lower the pressure resistance level. A 300-mesh sieve can fully disperse the agglomerates, ensuring a uniform and continuous coating layer, thereby obtaining the highest pressure resistance.

[0027] Summary, as attached Figure 1-4 Example 1 was characterized by cross-sectioning and EDS surface scanning. The coated metal soft magnetic powder prepared by the present invention has a clear core-shell structure: the Fe-based magnetic core is completely covered by a continuous and uniform composite insulating coating layer composed of P and Si elements, without any missing coating or local defects. The phosphate passivation layer formed by P elements and the silicon-based insulating layer formed by Si elements are distributed in a coordinated manner, which effectively isolates the magnetic core and provides excellent insulation performance and microstructure stability for the soft magnetic composite material, verifying the reliability and innovation of the coating process of the present invention.

[0028] The following points should be noted in this article: 1. The accompanying drawings of the embodiments disclosed herein only relate to the structures involved in the embodiments disclosed herein; other structures can be referred to in general design.

[0029] 2. Where there is no conflict, the embodiments of this disclosure and the features in the embodiments can be combined with each other to obtain new embodiments.

[0030] Although embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

Claims

1. A method for preparing a high-pressure-resistant and low-loss iron-nickel magnetic powder core, characterized in that: The method specifically includes the following steps: Step 1: Construction of inorganic reinforcement layer; FeNi50 alloy powder is mixed evenly with inorganic coating agent and solvent, and after baking and curing, and sieving and dispersing, composite powder A with inorganic reinforcement insulation layer coated on the surface is obtained; Step 2: Silicon source treatment: The composite powder A is mixed evenly with the silicon source coating agent and solvent, and after baking, curing, sieving and dispersing, a composite powder B with an inorganic reinforcing layer and a silicon source insulating layer successively coated on the surface is obtained. Step 3: Silicone resin coating; The composite powder B is mixed evenly with silicone resin binder and solvent, and after wet granulation, baking and pre-curing, and grading and sieving, granules with three layers of insulating structure are obtained on the surface. Step 4: Lubrication and molding; add lubricant to the granular material, mix evenly, and then cold press to obtain a magnetic core blank; Step 5: Heat treatment; The green core blank is placed in a protective atmosphere for annealing heat treatment to eliminate the internal stress of compression and to thermally convert the silicone resin into a heat-resistant insulating structure. After the heat treatment is completed, it is cooled with the furnace to obtain the finished iron-nickel magnetic powder core.

2. The method for preparing a high-pressure-resistant and low-loss iron-nickel magnetic powder core according to claim 1, characterized in that: The laser particle size D50 of the FeNi50 alloy powder is one or more of 3μm, 5μm, 10μm, 15μm, and 20μm.

3. The method for preparing a high-pressure-resistant and low-loss iron-nickel magnetic powder core according to claim 1, characterized in that: The inorganic coating agent in step 1 is one or more of phosphoric acid, zinc dihydrogen phosphate, aluminum dihydrogen phosphate, calcium phosphate, nitrate, silicate, malonic acid, and oxalic acid; the amount of inorganic coating agent added is 6-8 wt% of the FeNi50 alloy powder.

4. The method for preparing a high-pressure-resistant and low-loss iron-nickel magnetic powder core according to claim 1, characterized in that: The baking temperature in step 1 is 100~180℃, and the baking time is 0.5~2h; a 200~300 mesh sieve is used for sieving.

5. The method for preparing a high-pressure-resistant and low-loss iron-nickel magnetic powder core according to claim 1, characterized in that: The silicon source coating agent in step 2 is one or more of water glass, silicon dioxide, orthosilicate, silane coupling agent, and silica sol; the amount of silicon source coating agent added is 0.1~1wt% of the FeNi50 alloy powder mass, the baking temperature is 100~160℃, and the baking time is 0.5~2h; sieving is done using a 200~300 mesh sieve.

6. The method for preparing a high-pressure-resistant and low-loss iron-nickel magnetic powder core according to claim 1, characterized in that: The silicone resin in step 3 is one or more of methyl silicone resin, vinyl silicone resin, epoxy modified silicone resin, and phenyl silicone resin; the amount of silicone resin added is 1~1.5wt% of the FeNi50 alloy powder; wet granulation is performed using a 60~80 mesh sieve; the baking temperature is 50~100℃, and the baking time is 0.5~2h; the grading and sieving is performed using a 60~200 mesh sieve.

7. The method for preparing a high-pressure-resistant and low-loss iron-nickel magnetic powder core according to claim 1, characterized in that: The lubricant in step 4 is one or more of molybdenum disulfide, zinc stearate, mica powder, hexagonal boron nitride, and calcium stearate; the amount of lubricant added is 0.2~0.5wt% of the FeNi50 alloy powder mass; the cold pressing pressure is 13~18T / cm. 2 .

8. The method for preparing a high-pressure-resistant and low-loss iron-nickel magnetic powder core according to claim 1, characterized in that: The protective atmosphere in step 5 is a mixture of nitrogen and hydrogen, wherein the nitrogen flow rate is 10~20 m³ / h. 3 / h, hydrogen flow rate is 0.5~2m 3 / h; the annealing heat treatment temperature is 680~750℃, and the holding time is 0.5~2h.